KKN Sebagai Upaya Pengembangan Potensi Desa: Optimalisasi UMKM, Pendidikan, dan Lingkungan di Desa Cimenyan: Pengabdian - Sandi; Idham Nurcahya Muharam; Adhinda Adeliana Putri; Haqiqy Hakim; Anandha Pramudhita; Siti Salwa Az’Zahra; Alya Mustika; Aldi Tamangunde; Muhamad Ardho Surya Leksana; Ihsan Alfazri; Sindi Meilani Sinduano; Muhamad Ghozali; Subhanjaya Angga Atmaja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community empowerment has become a crucial issue in sustainable development, particularly in Indonesia where rural areas hold significant potential through the development of MSMEs, education, and environmental management. This article highlights the urgency of the Kuliah Kerja Nyata (KKN) or Community Service Program as a form of student engagement in optimizing village potential and addressing socio-economic gaps. The main objective of this study is to evaluate the role of the 12th group of Universitas Kebangsaan Republik Indonesia (UKRI) in 2025 in Cimenyan Village in strengthening community capacity through economic, social, and environmental programs. This study employed a qualitative approach with a descriptive method, utilizing observation, interviews, documentation, and thematic analysis. The findings indicate an increased awareness among MSME actors regarding branding and simple financial recording, improved motivation and participation of children and youth through interactive educational programs, and a growing awareness of waste management practices among the community despite challenges in consistency. The study concludes that KKN makes a significant contribution to strengthening local capacity while enriching academic literature on service-learning as a model of community empowerment. The implications of these findings emphasize the need for continuous mentoring and long-term monitoring to ensure sustained impact, as well as open opportunities for further research on collaborative strategies between academia and local communities in rural development.